Fatima Mernissi’s Historical-Critical Methodology Toward Misogynistic Hadiths and its Implications for Contemporary Hadith Studies - Umi Sumbulah; Siti Fatimatuz Zahroh (HUMANISMA : Journal of Gender Studies, 2026)
Contemporary hadith studies face persistent challenges related to the use of certain hadiths that are frequently interpreted and mobilized in gender-biased ways within Islamic discourse. Such interpretations not only shape gender relations in Muslim societies but also reinforce social inequality through the normative and ahistorical legitimation of religious texts. This article critically examines Fatima Mernissi’s historical-critical methodology toward so-called misogynistic hadiths and analyzes its implications for contemporary hadith studies. Employing qualitative library research, this study draws primarily on Mernissi’s Women and Islam: An Historical and Theological Inquiry, supported by classical hadith literature and recent scholarship on hadith methodology and Islamic gender studies. The article argues that Mernissi should not be understood as a rejecter of hadith, but rather as a critical examiner of their historical authority, transmission contexts, and socio-political functions. By integrating isnād criticism, socio-historical analysis, and an examination of power relations in the construction of hadith authority, Mernissi’s approach contributes to a more contextual and gender-sensitive reading of hadith. At the same time, this article demonstrates that her methodology remains in tension with classical hadith epistemology, particularly regarding the limits of historical contextualization. The study concludes that engaging critically with Mernissi’s approach offers an important methodological dialogue that enriches contemporary hadith studies without undermining the normative authority of the Sunnah.